THE INVESTIGATION OF TAXPAYER COMPLIANCE IN TAX AMNESTY - Diamastuti, Erlina; Hardanti, Kurniasari Novi (UNIVERSITAS NEGERI SURABAYA, 2019)
This study aims to interpret tax payer behavior in the implementation of tax amnesty with qualitative approach. The main data sources were 8 informants. The informant is a taxpayer both business and personal entity in Surabaya who have implemented the tax amnesty program in phase I and II, which starts in July 2016 until December 2016. The results of this study, first few informants disobedient in taxation liability. Second, tax amnesty has not made taxpayer obey yet. The conclusion is tax Amnesty is not a choice but a compulsion.